Detection of pathogenic bacteria isolated from raw vegetables (ulam) / Izzafaiqaainaa Mohd Nor - Mohd Nor, Izzafaiqaainaa (2017)
Raw vegetables or ulam are one of essential diets of human being and become a side dish in a daily plate. But, all these salad vegetables might be contaminated with pathogenic bacteria that can caused food borne illness. Three different types of ulam were selected from two different retail outlet located in Puncak Alam, Selangor and their bacteriological attributes were examined by using routine microbiological method. Twenty one of bacteria isolated from ulam were further investigated by using, polymerase chain reaction (PCR) assay targeting 16s rDNA gene. Total viable count (TVC) and total coliform count (TCC) in all three samples were both too numerous to count (TNTC) .The highest total staphylococcal count (TSC) was found in selom (4.0 x 106) followed by lettuce (3.8 x 106) and kacang botol (2.0 x 106). Twenty one bacterial isolates from three ulam samples have both gram positive and gram negative bacteria. More than four predominating bacteria are detected in the isolates which are Enterobacter spp., Citrobacter spp., Klebsiella spp., Staphylococcus aureus, Acinetobacter spp., and Bacillus spp. Bacterial identification by using 16s rDNA primer showed only Staphylococcus aureus was identified from the studied of bacterial isolates. Proper transportation, hygiene handling and proper storage are essential to prevent cross contamination of pathogenic bacteria in salad vegetables.